Veterinary and Public Health Emergency Preparedness Initiatives - Foley, Kaitlin (My University, 2020)
Public Health Activity-Fort Lewis encompasses the U.S. Army Veterinary Services throughout the states of Washington and Alaska. During my year-long APE, I worked with my preceptor to develop and enhance the Public Health Activity-Fort Lewis emergency management program at Joint Base Lewis-McChord, WA. The components of my experience included leading the Public Health Activity-Fort Lewis emergency management program, representing the unit at installation-level work groups at Joint Base Lewis-McChord, developing emergency preparedness resources for pet owners and veterinary teams, and supporting the First Year Graduate Veterinary Program capstone project. My primary objectives were to support pet owner preparedness and develop the Public Health Activity-Fort Lewis emergency management program. Completing this Applied Practice Experience provided me the opportunity to utilize my didactic MPH coursework in an impactful real-world program and to provide a positive and lasting benefit to future military emergency management.
Keywords: emergency; preparedness; military; client education